Review of Kinoshita Kabuki's “Sakurahime Azuma no Bunsho” (2023) (Sound Stage Screen, 2023)
Review of Kinoshita Kabuki, Sakurahime Azuma no Bunsho (The Scarlet Princess), Tokyio (Owlspot Theater) and Kyoto (ROHM Theater), February 2023.